LANGUAGE AND CULTURE: THE ROLE OF LANGUAGE AS AN EXPRESSION OF NATIONAL THINKING (International journal of artificial intelligence, 2025)
this article provides a comprehensive and expanded analysis of the close and intrinsic relationship between language and culture, particularly focusing on the role of language in shaping and reflecting national thought. It argues that language is not only a tool for communication but a sophisticated cultural mechanism that reflects the collective identity, values, and worldview of a people. By drawing upon linguistic, sociolinguistic, and cultural studies, the paper explores how national identity is preserved and transmitted through language. It also considers how globalization poses challenges and opportunities for the protection and development of national languages.